2011
DOI: 10.1039/c0cc03092a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of photoluminescent carbogenic dots using mesoporous silica spheres as nanoreactors

Abstract: A novel and facile approach for preparing hydrophilic carbogenic dots (CDs) has been developed with mesoporous silica spheres as nanoreactors by using an impregnation method. The resulting highly efficient photoluminescent CDs without any further treatment are monodisperse, photostable and of low toxicity, and show excellent luminescence properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
175
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(184 citation statements)
references
References 34 publications
2
175
0
7
Order By: Relevance
“…[11][12][13][14] Recently, it has been found that besides the traditional down-converted photoluminescence, CQDs also display excellent up-converted photoluminescence (UCPL), in which the emission wavelength is shorter than the excitation wavelength used. 15,16 Moreover, photoexcited CQDs can also act as excellent electron acceptors and electron donors, as the PL from CQDs can be quenched e±ciently by either electron donor or electron acceptor molecules in solution.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Recently, it has been found that besides the traditional down-converted photoluminescence, CQDs also display excellent up-converted photoluminescence (UCPL), in which the emission wavelength is shorter than the excitation wavelength used. 15,16 Moreover, photoexcited CQDs can also act as excellent electron acceptors and electron donors, as the PL from CQDs can be quenched e±ciently by either electron donor or electron acceptor molecules in solution.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical methods include electrochemical synthesis, [12][13][14] combustion and acidic oxidation, 15,16 hydrothermal and pyrolysis routes, 17 supported synthesis [18][19][20] and microwave/ultrasonic synthesis. 21,22 However, some drawbacks associated these methods include extensive post-synthetic purification, lack of control of CQD surface chemistry and sample polydispersity.…”
mentioning
confidence: 99%
“…Physical methods include arc discharge, 6 laser ablation/passivation 7,8 and plasma treatment. 9 Chemical methods include electrochemical synthesis, [10][11][12] combustion and acidic oxidation, 13,14 hydrothermal and pyrolysis routes, 15 supported synthesis [16][17][18] and microwave/ultrasonic synthesis. 19,20 However, 30 all these methods possess some drawbacks including, e.g.…”
mentioning
confidence: 99%